Navigating the storm of healthcare workers burnout in the COVID-19 era: a bibliometric analysis - Kumareswaran, Suriya; Sundram, Bala Murali; Naidu, Thaalitha (Faculty of Medicine, Universitas Trisakti, 2025)
The COVID-19 pandemic has imposed unprecedented challenges on healthcare systems globally, significantly impacting healthcare workers (HCWs) and intensifying the incidence of occupational burnout. Characterized by emotional exhaustion, depersonalization, and diminished personal accomplishment, burnout has been further exacerbated by pandemic-specific stressors such as resource limitations, fear of contagion, overwhelming workloads, and emotional fatigue. This bibliometric analysis systematically evaluated 2,043 peer-reviewed publications from 2019 onwards, retrieved from major databases including Web of Science, Scopus, and PubMed. Using tools such as VOS viewer, the study analysed keyword trends, author collaborations, citation metrics, and thematic clusters to map the evolving academic landscape surrounding HCWs burnout during COVID-19. The results revealed significant research diversity, with contributions from 11,156 unique authors and a collaboration index of 6.65, indicating robust interdisciplinary engagement. High research output and citation impact were observed in countries such as the United States, China, Italy, and the United Kingdom. Prominent themes included “COVID-19,” “burnout,” “mental health,” and “nurses,” highlighting the psychological toll on frontline professionals. Keyword co-occurrence and heatmap analyses demonstrated a shift in scholarly focus from the immediate crisis to long-term strategies for resilience and recovery. Despite these insights, notable disparities in research output persist, particularly in underrepresented regions such as France and several low- and middle-income countries. These imbalances may hinder the development of globally relevant, context-specific interventions. The study underscores the urgent need for inclusive, multidisciplinary collaboration to inform policy, guide mental health interventions, and enhance support systems for HCWs in current and future healthcare emergencies.